Streptococcus Mutans and Lactobacillus Species Infection in Obese and Non Obese School Children in Accra, Ghana - Ndanu, T.A.; Aryeetey, R.; Sackeyfio, J.; et al. (Journal of Obesity and Overweight, 2015)
Background: Streptococcus mutans and Lactobacillus species are major bacteria associated with dental caries. In the presence of fermentable sugars and poor oral hygiene, these bacteria increase the risk of caries. Some studies have associated obesity with dental caries while others did not. High-sugar snacks are risks for both obesity and dental caries. Citation: Ndanu TA, Aryeetey R, Sackeyfio J, Otoo G, Lartey A, et al. (2015) Streptococcus mutans and Lactobacillus Species Infection in Obese and Non-Obese School Children in Accra, Ghana. J Obes Overweig 1(1): 101 Objectives: This study aimed at determining Streptococcus mutans and Lactobacillus species infection and its relationship with dental caries among obese and non-obese children. Methods: Oral plaque was taken from 75 obese and non-obese children from private schools in Accra, Ghana. The plaque was pre-enriched in thioglycollate broth for 48 hours at 37 °C. Streptococcus mutants and Lactobacillus species were recovered after sub-culturing the broths onto Mitis Salivarius Bacitracin (MSB) and Man Rogosa Sharpe (MRS) selective plates, respectively, and incubation at 37 °C under anaerobic conditional morphology and catalase activity identified bacteriuria isolates on the selective privity. Results: Streptococcus mutans was isolated in 51 (33.6%) of all 150 children. The prevalence of Streptococcus mutans was significantly higher in the obese children 31 (41.3%) than the non-obese 20 (26.0%), p=0.033. Recovery of Lactobacillus species was low 2 (1.3%). Caries prevalence was similar in the obese 14.9% and non-obese 15.1%. There was no significant association between Streptococcus mutans infection and the dental caries. Overall Silness and LÖe Plaque Index of 1.1 ± 0.5 indicate good oral hygiene status for the children. Conclusion: Obese school children had higher oral Streptococcus mutans infections than non-obese children but this was not significantly associated with dental caries prevalence.
Research Article
Keywords: Streptococcus mutans; Lactobacillus species; Obese children; Dental caries; Accra